Engineering properties evaluation of unfired sludge bricks solidified by cement-fly ash-lime admixed nano-SiO2 under compaction forming technology. (30th October 2020) - Lang, Lei; Chen, Bing; Pan, Yongjian
Highlights: The unfired sludge bricks (USB) were prepared by chemical solidification and compaction forming technology. A series of physical, mechanical and thermal conductivity tests were conducted to evaluate the engineering properties of USB. The optimum compressive strength of USB was achieved by adding 1.5% nano-SiO2 . The microstructure and crystalline phases of typical USB were explored by conducting SEM and XRD tests. Abstract: This paper investigated the engineering properties of unfired sludge bricks (USB) made from dredged sludge and cement-fly ash-lime admixed nano-SiO2 binders under compaction forming technology. A series of laboratory tests were conducted to evaluate the effects of cement content, mass ratio of lime to fly ash (L/FA) and nano-SiO2 (NS) content on the physical, mechanical and thermal insulation performance of USB. Furthermore, scanning electron microscopy (SEM) and X-ray diffraction (XRD) tests were also performed to explore the microstructural properties of USB. The results indicated that the binder composed of 15% cement, 1% lime, 9% fly ash and 1.5% NS was recommended to replace 25% cement for preparing USB, which can increase 7-, 28- and 60-day compressive strength by 1.37, 12.94 and 23.30%, respectively. The bulk density of USB increased with the increase of cement and NS content, but decreased with the L/FA. The water absorption of USB decreased with increasing cement and NS content, but increased with the L/FA. The lime content used in USB should be less than 3%. The pH of USB decreased with increasing NS content, and tended to be stable as the NS content increased to more than 1.5%. The increase of cement and NS content had adverse effect on the thermal insulation performance, but this can be effectively improved by the inclusion of lime and fly ash. A positive linear relationship was achieved between thermal conductivity and bulk density. The microstructure analysis confirmed that the CSH and CAH gels were the main cementitious products inside the USB, and the calcite (CaCO3 ) may be responsible for the micro-cracks appeared in USB.